Application Bottlenecks and Solution Pathways of Steady-State Visual Evoked Potential-Based Brain- Computer Interface Systems - He, Zichen (Exploring Science Academic Conference Series, 2026)
Steady-state visual evoked potential (SSVEP) has become one of the mainstream paradigms in brain-computer interface (BCI) systems due to its high information transfer rate, high recognition accuracy, and low user training requirements. It has shown potenti al in medical rehabilitation and intelligent control. Despite substantial technical advances in laboratory settings, SSVEP -BCI systems still face significant bottlenecks when transitioning to real-world, everyday applications, resulting in limited practical deployment. This paper examines the current application status and challenges of SSVEP -BCI systems, systematically reviews their use in medical rehabilitation, and analyzes the core difficulties from technical, hardware, and user perspectives. At the technical level, the focus is on signal denoising and asynchronous system design. At the hardware level, the analysis centers on the trade -off between device cost and performance. At the user level, the discussion addresses core needs related to comfort and portability. In response to these challenges, the paper summarizes existing solutions, including fusion with electromyography (EMG) signals for denoising, sponge electrodes made from novel materials, high-frequency stimulation, and hybrid paradigms. The paper also highlights that algorithm optimization, new material development, and hybrid paradigms will be key pathways for moving SSVEP-BCI systems from laboratories to widespread application. This review summarizes current challenges and potential solutions for the practical deployment of SSVEP-BCI systems.